Avaliação da atividade antiacteriana in vitro e parâmetros envolvidos o reparo de lesões in vivo do mel de Jataí (Tetragonisca angustula) - Muniz, Elusca Helena (2023)
Bee honey has been used throughout history as a natural product with antibacterial properties and the ability to heal wounds. The bee Tetragonisca angustula, commonly known as the jataí bee, produces honey that not only exhibits antibacterial activity but also has moisturizing properties that contribute to healing. This study focused on jataí honey collected in Corumbaíba, Goiás, Brazil, investigating its antibacterial activity, anti-inflammatory properties, collagen biosynthesis, and its ability to close wounds in BALB/c mice.The evaluation of antibacterial activity was conducted in vitro using the disc-diffusion technique, with jataí honey tested at three concentrations: 100%, 75%, and 50%. The tested bacterial strains included Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Escherichia coli. Results were presented as the mean and standard deviation of the inhibition halos. In vivo analysis was performed on mice after 3 and 7 days of lesion induction, totaling 48 animals. Mice were divided into three groups: negative control (CO-) with untreated lesions, positive control (CO+) with lesions treated with 1% silver sulfadiazine, and the honey group (MEL) with lesions treated with jataí honey. Jataí honey was compared with both controls. Despite previous studies indicating antibacterial activity against the tested strains, this study did not observe bacterial inhibition. This discrepancy may be attributed to the acquisition of different strains or variations in the antimicrobial properties of honey from different geographical origins. However, treatment with jataí honey demonstrated a reduction in neutrophils compared to the positive control, along with an increase in macrophages, mast cells, angiogenesis, collagen deposition, and a shorter time required for lesion closure compared to untreated lesions. These results suggest that jataí honey could be a promising therapeutic alternative for wound healing.